Progresivitas Kecerdasan Buatan dalam Perspektif Epistemologi: Progressiveness of Artificial Intelligence in Epistemological Perspective - Mellyzar, Mellyzar; Nahadi, Nahadi; Nabuasa, Desi Aryanti (Undiksha, 2024)
Artificial Intelligence (AI) is advancing rapidly, and the increasing reliance on AI technology brings several advantages, such as improved efficiency, enhanced personalization, and smarter decision-making. However, this growing dependency also raises concerns regarding the epistemological foundations of AI. This study aims to examine the epistemology of AI development through qualitative research using a literature review approach. AI is a fusion of science and technology. Classical sources of knowledge, such as sensory experience, rationality, and testimony, remain crucial in human efforts to understand reality, despite AI offering sophisticated tools for data analysis and prediction. The knowledge produced by AI is complex and varies depending on the context and the type of system employed. AI’s complex algorithms, often perceived as a